The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1124/jpet.105.088153
|View full text |Cite
|
Sign up to set email alerts
|

The Histaminergic Signaling System Exerts a Neuroprotective Role against Neurodegenerative-Induced Processes in the Hamster

Abstract: The neurotoxic 3-nitropropionic acid (3-NP), a freckled milk vetch-derived inhibitor of mitochondrial enzymatic processes that is capable of mimicking the typical pathological features of neurodegenerative disorders, behaved in a differentiated manner in a hibernating rodent (hamster) with respect to a nonhibernating rodent (rat). Treatment of the two rodents with both an acute and chronic 3-NP dose supplied deleterious neuronal effects due to distinct histamine receptor (H n R) transcriptional activities, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In addition, this pattern was correlated to that of both ERa and ERb as well as ERK1/2 considering the protective roles exerted by these factors against excitotoxicity events in cortical and hippocampal neurons (Nilsen & Diaz 2003). Overall, the resulting sexually dimorphic distribution pattern of GPR30 expressing neurons could nicely represent a starting point regarding its role not only on estrogen functions in the absence of ERs, but also on ischemic-like events that are evoked in hibernators during arousal (Canonaco et al 2005).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, this pattern was correlated to that of both ERa and ERb as well as ERK1/2 considering the protective roles exerted by these factors against excitotoxicity events in cortical and hippocampal neurons (Nilsen & Diaz 2003). Overall, the resulting sexually dimorphic distribution pattern of GPR30 expressing neurons could nicely represent a starting point regarding its role not only on estrogen functions in the absence of ERs, but also on ischemic-like events that are evoked in hibernators during arousal (Canonaco et al 2005).…”
Section: Introductionmentioning
confidence: 78%
“…This feature is sustained by the expression of GPR30 not only in ER-enriched areas and so tends to further corroborate its critical role in the estrogen actions above all in facultative hibernators. Studies in our animal model are only at the beginning and further interests especially during the different hibernating states could prove to be useful for the unveiling of pathological processes such as ischemia that occurs during the arousal phase (Canonaco et al 2005) of this particular physiological condition.…”
Section: Discussionmentioning
confidence: 99%
“…thioperamide and ABT-239, have been revealed in in vitro and in vivo kainic acid-or 3-nitropropionic acid (3-NP)-induced neurotoxicity models [113,114]. In a previous study, upregulation of H3Rs down-regulation of H1Rs have been found to coincide with excessive neuronal damage and behavioral effects as a consequence of 3-NP-induced neurotoxicity in hamster and rat [115]. Moreover, another interesting H3R antagonist, namely JNJ-5207852, was found to ameliorate different memory deficits induced by PTZ kindling in weanling mice [116].…”
Section: Alzheimer's Diseasementioning
confidence: 96%
“…We used neurons isolated from hippocampus, which is an important brain area owing to its vital role in the consolidation of several forms of learning and memory and especially during the formation of declarative memories [16,17]. Hippocampal neurons, which are well known for their plasticity and regeneration properties [18], are the best-characterised model for investigating polarization that occurs spontaneously during the first days of culture [19][20][21].…”
Section: Introductionmentioning
confidence: 99%